Efficacy of pulsed electric fields and antimicrobial compounds used alone and in combination for the inactivation of Campylobacter jejuni in liquids and raw chicken. (January 2020) - Clemente, I.; Condón-Abanto, S.; Pedrós-Garrido, S.; Whyte, P.; Lyng, J.G.
Abstract: This work evaluated the bactericidal effects of a number of essential oils (EOs), organic acids and pulsed electric fields (PEF) against a range of Campylobacter jejuni strains. C. jejuni (1146DF) was found to be the most PEF resistant strain, and was chosen to evaluate the combination of PEF and oregano EO (the most effective compound). Simultaneous PEF/oregano treatments in liquid showed no significant increase in levels of inactivation when compared to reductions achieved for individual PEF treatments (p > 0.05). However, in a sequential combination approach, PEF treatment followed by re-suspension in oregano produced significant increases in inactivation levels at all field strengths tested (p < 0.05). ¼ MIC of oregano was determined as the minimum concentration required to obtain maximum microbial inactivation using sequential combinations. PEF was then applied to raw chicken using different field strengths 0.25–1 kV/cm, followed by re-suspension in ¼ MIC of oregano. Application of 1 kV/cm in chicken followed by resuspension achieved a reduction close to 1.5 Log10  CFU/g, and also showed synergistic behaviour. The results obtained in this work would open the possibility of using this combination for chicken decontamination, because the inactivation achieved was in the same range as those obtained using conventional thermal treatments. Highlights: Combined treatment of PEF and Oregano EO shown indifferent interactions in liquid. Higher inactivation of C. jejuni were observed when electric field strength raised. Combination subsequent of PEF and Oregano EO was synergistic in liquid and chicken. Combination subsequent of PEF and Oregano EO could be used to decontaminate chicken. Pulsed Electric Fields technology proved to be effective for chicken decontamination.